(untitled) (International Educators Conference, 2025)
This article examines the trends, characteristics, and prospects of artificial intelligence (AI) development in the countries of Central Asia. It analyzes national digital transformation strategies, scientific and educational initiatives, as well as the role of international cooperation in advancing AI technologies. Special attention is given to Uzbekistan, Kazakhstan, and Kyrgyzstan as countries demonstrating active policies in digitalization and innovation.